Catalytic Oxidation of Aqueous Sulfide Promoted by Oxygen Functionalities on the Surface of Activated Carbon Briquettes Produced from Viticulture Wastes - Deiana, Ana C. (2014)
In this work, the catalytic oxidation of the hazardous and unpleasant aqueous sulfide contaminant was investigated by activated carbon in the form of mechanically resistant and versatile briquettes produced from two different wastes of the wine industry, i.e., lex and stalk. Characterization by scanning electron microscopy with energy dispersive X-ray spectroscopy (SEM/EDS), surface area Brunauer-Emmett-Teller (BET), Raman, thermogravimetry (TG), X-ray diffractometry (XRD) and potentiometric titration showed that the materials have high mesoporous area with a large number of surface oxygen functionalities. These briquettes showed high efficiency for the oxidation of sulfides in aqueous medium, which is discussed in terms of two effects: the relatively high concentrations of quinone/hydroquinone surface redox groups formed from the grape must binder and the macro/mesoporosity, which facilitates the diffusion of the different species during the reaction.